Biochemistry - Voet, Donald Voet, Judith G (Wiley, 2011)
The "Gold Standard" in Biochemistry text books, Biochemistry 4e, is a modern classic that has been thoroughly revised. Don and Judy Voet explain biochemical concepts while offering a unified presentation of life and its variation through evolution.